Testosterone, cortisol, vitamin D and oxidative stress and their relationships in professional soccer players - Abate, M.; Di Carlo, L.; Cocco, G.; Cocco, A.; Salini, V. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: The testosterone/cortisol ratio has been used in sport physiology to evaluate the balance between anabolism and catabolism; its decrease below 30% has been considered a marker of overtraining. In this framework recent studies in soccer players have investigated the relationships between testosterone, cortisol, vitamin D and reactive oxygen species, but with unconvincing results. The aim of the present study was to evaluate the behavior of such biological parameters and their relationships both in winter (the season of championship) and in summer (off-competition season), characterized by different homeostatic situations. METHODS: Twenty-seven professional male football players (Second Italian Division), were studied. Blood levels of free testosterone, cortisol, vitamin D and reactive oxygen species were evaluated in August (pre-season training) and in February, in the midseason. A comparison between these two periods was performed and for each of them the relationships between the biological parameters were evaluated. RESULTS: Blood levels of testosterone were higher during summer whereas those of cortisol were higher in winter. Vitamin D levels were higher in summer; in this season a positive significant relationship between vitamin D and testosterone was observed (P=0.001), but not in winter (P=0.592). Reactive oxygen species were higher in winter; in this season a significant positive relationship between these substances and cortisol was observed (0.000), but not in summer (P=0.325). CONCLUSIONS: In professional soccer players it was found a positive relationship between vitamin D and testosterone in summer and between reactive oxygen species and cortisol in winter. However, the question whether such results are genuine cause-effect relationships or mere casual or spurious statistical correlations is still unsolved. As matter of fact, such results could be dependent from other determinants which might drive the aforementioned biological parameters in the same direction. These conclusions must be considered valid only in relation to the experimental conditions (training workload, diet and sun exposure) of the present study.